PEMIDANAAN TERHADAP DELIK PEMBAYARAN UPAH DI BAWAH UPAH MINIMUM DALAM RANGKA MENCAPAI TUJUAN PEMIDANAAN DI INDONESIA - Jeremy Nicholas; Ade Adhari (Fakultas Hukum Universitas Tarumanagara, 2021)
This research is a normative legal research by collecting data on criminal decisions on the issue of paying wages below the minimum limit for workers in Indonesia. This study uses a legal approach and a case approach that is related to the problems in this study, which are criminal cases regarding the offense of paying wages below the minimum wage which are less effective in comparison with civil cases or Industrial Relation Disputes which are aimed at achieving the objectives of punishment in Indonesia. . The purpose of punishment is as a deterrent effect, coaching and educating the perpetrators so that they do not repeat their actions again and become better individuals in carrying out their lives so as to create security and protection for the people in Indonesia. This offense has been regulated that the act is a criminal offense whose criminal sanctions have been regulated in the Manpower Act which was updated in the Job Creation Law by applying special minimum criminal sanctions, but due to the lack of understanding of the legal apparatus in the field of labor crime and even the labor criminal desk which had been formed at Polda Metro Jaya did not work as expected because its function was only to consult law and direct the case to the Industrial Relation Disputes.